Activity Red Moringa oleifera Leaf Extract As a Preventive Measure on the Proﬁle of CD4+CD62L+and CD8+CD62L+Cells in BABL/c Mice Injected Salmonella typhimurium - Wuryandari, MM Riyaniarti Estri; Widodo, Widodo; Widjajanto, Edi; Rifa’i, Muhaimin (KnE Social Sciences, 2019)
Moringa oleifera has both nutritional and complex phytochemical content which provideprotectionandrecoveryfrominfection.Moringa oleiferahasthepotentialasan immunomodulator both in preventive and curative measures. Salmonella typhimurium can cause body immunity, especially CD4+CD62L+ and CD8+CD62L+ T cells have a deﬁciency so that Salmonella typhimurium can infect body cells. This researched aims to determine whether the administration of Moringa oleifera leaves extract can increase the number of T CD4+CD62L+ and CD8+CD62L+cells in mice infected by Salmonella typhimurium. This experiment used was a complete randomized factorial pattern design. Mice were divided into two groups, namely the control group (positive control and negative control) and the infection group, mice (given Moringa oleifera leaves extract dose of 14 mg/kg BW, 42 mg/kg BW, and 84 mg/kg BW) and infected by Salmonella typhimurium. Data analysis was conﬁrmed with the ANOVA test followed by Tukey test (p<0.05). The results showed that red Moringa oleifera leaves extract can increase the number of CD4+CD62L+ and CD8+CD62L+ T cells in all groups of infected mice and of Moringa oleifera leaves extract with high doses caused immunosuppression. Red Moringa oleifera leaves extract can function as an immunostimulant and immunosuppression on CD4+CD62L+and CD8+CD62L+T cells. Keywords: CD4+CD62L+ , CD8+CD62L+ , Moringa oleifera, Salmonella typhimurium